The Influence of Kahoot and Conventional Technology-Based Learning Media on Learning Outcomes in Accounting Practicum - Elvina Evaalfasalni H; Supriyadi Supriyadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Technology is very important to support learning process. This study aims to reveal Kahoot Technology-Based Learning Media (X) on student learning outcomes at SMK NEGERI 8 Bekasi City (Y). This study uses a type of quantitative research with an experimental approach. The sample of this research used random sampling technique. The number of research samples was 69 students. Data collection uses valid and reliable instruments. Data analysis using simple regression. The results of the study revealed: (1) Linear Regression Equation Y = 82.341 + 0.049 X (2) Kahoot Technology-Based Learning Media has an effect on Student Learning Outcomes. (3) The significance test obtained by the equation of the F hit regression line is smaller than 0.05 thus, Y or X regression is significant Kahoot Technology-Based Learning Media has an effect on Student Learning Outcomes. (4) The correlation coefficient (rxy) = 0.621 and Fhit (Fchange) = 8.145, with a pvalue less than 0.05. Thus, the correlation coefficient X and Y is meaningful or significant. The coefficient of determination is 0.385, which means that 38.5% of the variation in the student's emotional intelligence variable.